Information on the larger grain borer - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
leaflet on the larger grain borer has been produced by the Group for Assistance on Systems Relating to Grain After Harvest (GASGA) and the Natural Resources Institute (NRI) and published by CTA